Practical approaches to pedagogically rich online tutorials in health professions education - Amy Seymour-Walsh; Anthony Weber; Andy Bell (James Cook University, 2020)
Health professions education in tertiary, industrial and other contexts often entails face-to-face small group learning through tutorials. The current novel coronavirus, COVID-19, has reduced face-to-face contact, and this has challenged how health professionals and clinical students can access training, accreditation and development. Online and other remote mechanisms are available to tutors and course designers; however, they might not feel comfortable with such affordances, in light of expectations to so rapidly change familiar teaching and delivery styles. This may result in the loss of interaction and disruption of peer learning, which are hallmarks of the small group tutorial. Collaborative learning is essential to develop and refine an emerging sense of belonging to a professional community through formal studies, and interactive learning is a requirement for some registered health professions to satisfy ongoing professional accreditation. Online media has been used to promote social learning in regional, rural and remote communities for some time. Strategies for learning activity design and tutor training are proposed to equip course designers and educators to support health professions education remotely, through the synchronous, online small group. This may herald a new era of increased access to training and professional development for non-urban learners, beyond COVID-19.